2022
DOI: 10.1017/ash.2022.274
|View full text |Cite
|
Sign up to set email alerts
|

Impact on time to active antimicrobial therapy with 24-hour pharmacist review of Accelerate Pheno BC Kit results

Abstract: The Accelerate Pheno platform provides rapid identification and susceptibility data. We demonstrate successful incorporation of 24-hour pharmacist review of Accelerate Pheno results that reduced the number of patients going >3 hours from result without an order for active antimicrobial therapy from 29 (2.8%) of 1,043 to 9 (0.85%) of 1,053 (P < .001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…The implementation of our antimicrobial scoring system also had no effect on time to effective antibiotic therapy. Kinn et al 7 showed that 24-hour pharmacist review of rapid diagnostic blood culture results decreased the incidence of patients receiving ineffective therapy, which our study did not find. However, in our study 74.5% of patients were receiving effective therapy at the time the culture resulted, limiting the possibility of pharmacist intervention.…”
Section: Discussionsupporting
confidence: 92%
“…The implementation of our antimicrobial scoring system also had no effect on time to effective antibiotic therapy. Kinn et al 7 showed that 24-hour pharmacist review of rapid diagnostic blood culture results decreased the incidence of patients receiving ineffective therapy, which our study did not find. However, in our study 74.5% of patients were receiving effective therapy at the time the culture resulted, limiting the possibility of pharmacist intervention.…”
Section: Discussionsupporting
confidence: 92%